If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 2x = -5 + x + -3 Reorder the terms: -6 + 2x = -5 + -3 + x Combine like terms: -5 + -3 = -8 -6 + 2x = -8 + x Solving -6 + 2x = -8 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -6 + 2x + -1x = -8 + x + -1x Combine like terms: 2x + -1x = 1x -6 + 1x = -8 + x + -1x Combine like terms: x + -1x = 0 -6 + 1x = -8 + 0 -6 + 1x = -8 Add '6' to each side of the equation. -6 + 6 + 1x = -8 + 6 Combine like terms: -6 + 6 = 0 0 + 1x = -8 + 6 1x = -8 + 6 Combine like terms: -8 + 6 = -2 1x = -2 Divide each side by '1'. x = -2 Simplifying x = -2
| 6x+36=48 | | 4t+.2=1.3 | | 2/3+2/3=n | | 6x+8=3x-20 | | 6x-8=3x-20 | | -2(y+7)=-4-16 | | 6x+1=7-6x | | 75x+15=25x | | 2x-5+4x+15+y=180 | | 3a+4+2a=2(5a-3) | | 6x+10+y=180 | | 1(-4)= | | 150(t)=16.1t^2+150 | | y=10x+11 | | 6(x+2)=26 | | 0=r^2-37.21 | | (-6)= | | 25.12=1/3(12.56h) | | 4z+9=0 | | 8(1-5v)-2=-274 | | 90=-6(3-3n) | | 6(2n+3)= | | 8(-8x-3)=232 | | 15=2x^2+5x-3 | | 4x+5y=103 | | 6+6(1+7a)=306 | | lxI+3=8 | | 0=-10x^2+3x+27 | | 4(x+10)(x-5)=0 | | -2y+4(8y-7)=4+9(-9-y) | | y=-0.05x^2+0.7x | | 14x-225=5x-9 |